Closing the Second-Level Digital Divide: An Analysis of Digital Literacy Interventions and Their Effect on Educational Outcomes in Rural Communities - Laura Lehtonen; Jari Koskinen; Katri Salo (Journal of Social Science Utilizing Technology, 2025)
Background. The digital divide remains a significant challenge, particularly in rural communities, where limited access to technology and digital resources exacerbates educational inequities. While the first-level digital divide focuses on access to technology, the second-level digital divide addresses disparities in digital literacy the ability to effectively use digital tools to enhance learning. This study explores the effectiveness of digital literacy interventions in rural communities and their impact on educational outcomes. Purpose. The primary objective of this research is to assess how targeted digital literacy programs can improve students’ learning experiences and academic performance in rural areas. Method. A mixed-methods approach was employed, combining quantitative analysis of academic performance data with qualitative interviews from students, teachers, and community stakeholders. Results. The findings reveal that digital literacy interventions significantly enhance students' technological proficiency, with improvements in both their academic performance and engagement with digital learning platforms. However, the study also identifies challenges related to the sustainability of these programs and the need for continuous support. Conclusion. In conclusion, this research underscores the importance of bridging the second-level digital divide through comprehensive digital literacy initiatives, which can help mitigate educational disparities in rural communities and contribute to long-term improvements in educational equity.